Early Sexual Initiation Among Adolescent Girls in Indonesia - Aenaya Delavera; Tris Eryando (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2021)
Early sexual initiation is a public health problem and is now common worldwide, especially in developing countries. This can have many negative impacts on female adolescence, so it is very important to do prevention. This study aimed to determine the determinants of early sexual initiation among female adolescence in Indonesia. The subjects of the study were never-married women aged 15 – 24. This research was quantitative using secondary data from the 2017 Indonesia Demographic and Health Survey (IDHS) with a cross-sectional research design. The results of the logistic regression showed that age, education, alcohol consumption, smoking, peer influence, boyfriend ownership, wealth, and media exposure were associated with early sexual initiation. Peer influence (AOR=27,127; p < 0.001) and education (AOR=10,909; p=0.003) are the most dominant factors were associated with early sexual initiation. This study suggests the establishment of a comprehensive reproductive and sexual health (RSH) education mechanism both inside and outside schools; use the media to reach a wider range of youth, and programs to assist parents in optimizing their role in supervising adolescence.